Reporting the real names of juvenile offenders: a study of Japanese perspectives through the lens of symbolic discrimination - Watamura, Eiichiro (International journal of law, crime and justice, 2023)
This study examined Japanese attitudes toward reporting the real names of juvenile offenders, through the lens of symbolic discrimination. This topic has attracted much attention in recent literature. As extant research suggests that the Japanese public considers Japan's Juvenile Law to be outdated, we hypothesized that the notion of symbolic discrimination—which argues that juveniles should not be treated differently from adults—would be related to attitudes toward real-name reportage. After an online survey of 961 Japanese people aged 14 years and older, a multiple regression analysis was conducted to investigate attitudes toward real-name reportage of and symbolic discrimination against juvenile offenders, including appropriate punishment for bad behavior (balance) and adversity experienced by juvenile offenders (adversity). The results showed that, in addition to several of the participants' beliefs about and perceptions of juvenile offenders and crimes, balance was associated with support for real-name reportage, demonstrating that symbolic discrimination was related to support for the same.